Strategi Madrasah dalam Meningkatkan Daya Saing dan Minat Peserta Didik pada Era Digital di MA Ar-Rusdiny NW Segaet Desa Wakan: Madrasah's Strategy in Increasing Student Competitiveness and Interest in the Digital Era at MA AR-Rusdiny NW Segaet - Zakaki; Ozi Satria; M. Anwar Azizul Azim; Moh. Irwan Azhari; Muh. Zainil Rahman (Al-Gafari : Manajemen dan Pendidikan, 2026)
Digital information technology has become a digital marketing medium for educational service institutions, in introducing and improving the image of education. This study aims to describe the strategies implemented by MA Ar-Rusdiny NW Segaet to increase the competitiveness and interest of new students in the digital era and identify obstacles and solutions encountered in its implementation. This study uses a qualitative approach with a case study method. Data were collected through interviews, observations, and documentation, and analyzed using the Miles and Huberman model, which includes data reduction, data presentation, and drawing conclusions. The results show that the strategies used by the madrasah to increase the number of students include a socio-religious approach through active participation in community activities, the use of social media by teachers, and the dissemination of personal and emotional information to prospective parents. This strategy is considered effective because it strengthens community trust in the madrasah. Obstacles faced include limited facilities, low digital literacy, teacher discipline, and the economic conditions of the surrounding community. As a solution, the madrasah implemented a discipline reporting system that involves students, provides assistance to underprivileged students, and strengthens the emotional bond between the madrasah and the community. This study concludes that strategies based on socio-religious values ​​and a family-like approach are key to increasing the competitiveness and interest of students in rural areas, especially in the digital era.